Common Dermatophytosis: Scenario of Bangladesh and Their Management - Khan , Md Uzira Azam (Bangladesh Journal of Medicine, 2024)
Dermatophytosis is one of the skin diseases caused by dermatophyte fungi. Dermatophytes cause tinea pedis, tinea corporis, tinea cruris, tinea capitis, tinea unguium, tinea manum etc. They mainly occur in tropical countries like Southeast Asia. The prevalence of dermatophytosis ranges 20%-25%. Dermatophytosis typically presents as a well-demarcated, sharply circumscribed, mildly erythematous, pruritic scaly patch or plaque with a raised edge. The lesions may become widespread and invasive. It has significant negative social, psychological, and occupational health effects. The diagnosis is often clinical but in some cases the diagnosis requires microscopic examination, culture and PCR assay for fungal DNA of skin scrapings. Currently, dermatologists are facing a devastating situation with cases of dermatophytosis presenting with unusually large and atypical lesions making diagnosis difficult and has created a real panic among them. As enough research is not done in this area, hence it poses a therapeutic challenge to practitioners. American Academy of Dermatology guidelines on dermatophytosis were published two decades ago and the British Association of Dermatology focused only on tinea capitis and onychomycosis. Also, the treatment in the textbooks is not updated. Bangladesh has not yet produced any guideline on this issue. Indian Expert Forum Consensus Group recommended treatment for dermatophytosis recently. It recommended treatment as follows: (i) tineapedis: terbinafine (250 mg/day) in naïve cases for 2-4 weeks, or itraconazole (200 mg - 400 mg/day, in divided dose) in recalcitrant/ severe cases for >4 weeks; (ii) tineacruris and corporis: topical antifungal agents (azoles) in naïve cases. Extensive or recalcitrant infection require oral combination therapy: terbinafine (250 mg/day) and itraconazole (100 mg-200 mg/day) in naïve cases. In recalcitrant cases, itraconazole (200 mg-400 mg/day, in divided dose) along with topical therapy for 2–4 weeks in naïve cases, 4 weeks in recalcitrant cases: (iii) tinea incognito: abrupt withdrawal of steroids and oral itraconazole 200 mg-400 mg daily for 4-6 weeks or longer are suggested: (iv) Onychomycosis: Terbinafine 250 mg/day for 6 weeks in fingernail and 12-16 weeks in toenail infection. Itraconazole 200 mg per day for 12 weeks continuously, or alternatively as pulse therapy at a dose of 400 mg per/day for 1 week/month for 2 pulses for fingernail 3 pulses for toenail. Treatment should be continued for 2 weeks after clinical cure. Baseline LFTs and periodic follow-up should be done. With the current situation, Indian dermatologists use higher doses, longer duration and combination of oral antifungals for the management of recalcitrant cases. Griseofulvin and fluconazole are used in patients where terbinafine or itraconazole had failed. Use of keratolytics (except folds and face), moisturizers, calcineurin inhibitors, desiccant powder and antihistamines have been suggested. Avoidance of tight-fitting and non-cotton clothing, treating close contacts, and avoidance of body contact sports are important inputs to be counselled. In elderly patients, the presence of comorbidities and the possibility of drug interactions should be considered. For pediatrics topical agents are recommended. Oral fluconazole (from infancy) and terbinafine (>2 years old) are recommended. In pregnancy topical antifungals are given at any stage of pregnancy but all systemic antifungals are avoided except terbinafine which is pregnancy category B. Being absence of guideline in Bangladesh, anybody is giving treatment of dermatophytosis. Recognized dermatologist follows textbooks’ and journals’ recommendation as they like best. People use different systemic and topical antifungals in haphazard manner. The topical agents are mostly mixed with steroids which suppresses the disease temporarily but converts it tinea incognito. They also use medications without indication leading to severe acute irritant contact dermatitis. Inadequate dose and duration of antifungals and use of steroids and irrational medicine cause recurrence of the disease. Patients should consult a dermatologist as soon as dermatophytosis is noticed in any part of the body. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 136-137